414 Enhancing T cell therapy for patients with relapsed/refractory Wilms tumor. (10th December 2020) - Hont, Amy; Cruz, Conrad; Stanojevic, Maja; Ulrey, Robert; Terpilowski, Madeline; Reynolds, Emily; Hoq, Fahmida; Fortiz, Maria; Lang, Haili; Dome, Jeffrey; Hanley, Patrick; Bollard, Catherine; et al.
Abstract : Background: Patients with relapsed or refractory Wilms tumor (WT) have poor prognoses with limited treatment options. 1–3 Immunotherapy offers a promising alternative for targeted therapy but has been limited by immune evasion tactics. 4–6 Adoptive cell therapy with patient-derived tumor-associated antigen-specific T cells (TAA-T) targeting 3 antigens (WT1, PRAME, and survivin) has the potential to overcome antigen loss. The objective of this phase I clinical trial is to determine the safety of administering TAA-T to patients with high-risk, relapsed/refractory solid tumors. Secondary objectives include determination of clinical efficacy and immunobiology following infusion. Methods: T cells expanded from patient peripheral blood are stimulated weekly with antigen presenting cells expressing an overlapping peptide library spanning the tumor antigens WT1, PRAME, and survivin. Following release testing, patients are infused with TAA-T on a dose escalation study, ranging from a dose of 1 x 107/m 2 (dose level 1) to 4 x 107/m 2 (dose level 3). Clinical and immunobiological studies performed post-infusion monitor for adverse effects and assess immune and disease responses. Results: Therapy with TAA-T was shown to be safe and well-tolerated in patients with high-risk solid tumors on this dose-escalation study. 7 A total of 18 patients have been infused, with WT as the predominant diagnosis, accounting for 10 patients. We elucidated a dose-response relationship, with a prolonged median time to progression for patients treated on dose level 3 (recommended dose level [RDL]) compared to those on dose level 1 and 2 combined (5.2 vs 2.8 months, respectively) (figure 1 ). Patients demonstrated prolonged progression-free survival (PFS) compared to therapy received just prior to TAA-T (figure 2 ). Best response observed was stable disease. A majority of patients demonstrated improved anti-tumor immunity as evidenced by antigen spreading (figure 3 ). Conclusions: In long-term follow up, the 1-year progression-free survival (PFS) remains improved for patients treated at the recommended dose level compared to the PFS observed with therapy received immediately prior to TAA-T (29% vs 15%, respectively). Three patients are long-term (28–38 months) survivors without disease progression or further therapy. This unique immunotherapeutic has been well-tolerated without life-threatening cytokine release syndrome. To enhance TAA-T activity further in vivo, we will evaluate the safety of prescribed lymphodepletion prior to TAA-T infusion and assess anti-tumor immunity. We expect that lymphodepletion will enhance T cell persistence and expansion and recruit endogenous immune response with altered kinetics. Ethics Approval: The study was approved by the Children's National Hospital Institutional Review Board, approval number NCT02789228 . References: Dome JS, Graf N, Geller JI, Fernandez CV, Mullen EA, Spreafico F, Van den Heuvel-Eibrink M, Pritchard-Jones K. Advances in Wilms Tumor Treatment and Biology: Progress Through International Collaboration. J Clin Oncol 2015;33(27):2999–3007. Mullen EA, Chi YY, Hibbitts E, Anderson JR, Steacy KJ, Geller JI, Green DM, Khanna G, Malogolowkin MH, Grundy PE and others. Impact of Surveillance Imaging Modality on Survival After Recurrence in Patients With Favorable-Histology Wilms Tumor: A Report From the Children's Oncology Group. J Clin Oncol 2018:JCO1800076. Malogolowkin MH, Hemmer MT, Le-Rademacher J, Hale GA, Mehta PA, Smith AR, Kitko C, Abraham A, Abdel-Azim H, Dandoy C and others. Outcomes following autologous hematopoietic stem cell transplant for patients with relapsed Wilms' tumor: a CIBMTR retrospective analysis. Bone Marrow Transplant 2017;52(11):1549–1555. Heczey A, Louis CU. Advances in chimeric antigen receptor immunotherapy for neuroblastoma. Discov Med 2013;16(90):287–94. Park JR, Digiusto DL, Slovak M, Wright C, Naranjo A, Wagner J, Meechoovet HB, Bautista C, Chang WC, Ostberg JR and others. Adoptive transfer of chimeric antigen receptor re-directed cytolytic T lymphocyte clones in patients with neuroblastoma. Mol Ther 2007;15(4):825–33. Lamers CH, Sleijfer S, van Steenbergen S, van Elzakker P, van Krimpen B, Groot C, Vulto A, den Bakker M, Oosterwijk E, Debets R and others. Treatment of metastatic renal cell carcinoma with CAIX CAR-engineered T cells: clinical evaluation and management of on-target toxicity. Mol Ther 2013;21(4):904–12. Hont AB, Cruz CR, Ulrey R, O'Brien B, Stanojevic M, Datar A, Albihani S, Saunders D, Hanajiri R, Panchapakesan K and others. Immunotherapy of relapsed and refractory solid tumors with ex vivo expanded multiantigen-associated specific cytotoxic T lymphocytes: A Phase I Study. J Clin Oncol 2019:JCO1900177.